Opportunities for curriculum improvement in secondary school mathematics education - Eric Machisi; Benjamin Tatira (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
This study investigates opportunities for enhancing the secondary school mathematics curriculum in South Africa. Employing a cross-sectional survey design, data were collected from a purposive sample of 80 postsecondary students enrolled at higher education institutions across the country. An online questionnaire was administered, and responses were analyzed using the Statistical Package for the Social Sciences (SPSS), focusing on frequency distributions and mean ranks. The findings reveal that while the current mathematics curriculum adequately prepares some students for postsecondary studies, it falls short for others. Key areas identified for improvement include better alignment with tertiary-level mathematics, reforming examination formats, enhancing pedagogical approaches, and increasing collaboration with local industries. Based on these insights, the study proposes several recommendations: offering specialized mathematics tracks, including optional exam questions, reducing exam length, introducing calculus prior to Grade 12, integrating digital tools in instruction, and connecting mathematical learning with real-world industry applications. By foregrounding students’ perspectives, this research promotes a bottom-up approach to curriculum development. The study contributes to the literature by providing empirical evidence on curriculum gaps from the learner’s viewpoint and offering context-specific recommendations to bridge secondary and tertiary mathematics education in South Africa.